Prevalence Analysis of WSSV (White Spot Syndrome Virus) in Vaname Shrimp (Litopenaeus vannamei) in Bengkalis District - Akbar, Sidiq Malik; Effendi, Irwan; Feliatra, Feli; Muhson, Nanang (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
Vannamei shrimp (Litopenaeus vannamei) is one type of shrimp that is widely cultivated in Indonesia. Vannamei shrimp dominates aquaculture in Indonesia which was previously dominated by tiger shrimp (Penaeus monodon). WSSV, a double-stranded circular DNA virus, has become one of the most widespread and fatal diseases in shrimp populations. Therefore, it is necessary to conduct research to detect the WSSV virus that attacks white vaname shrimp and determine the prevalence rate of the WSSV virus that attacks white vaname shrimp in Bengkalis Regency. This study was conducted from February to June 2022. The purpose of this study was to analyze the prevalence rate of the WSSV virus that attacks white shrimp in the Bengkalis Regency. The research method used in this study is a survey method. The results of the morphological examination did not show any clinical symptoms in vaname shrimp. Tests using PCR with specific primers measuring 941 bp showed DNA bands of vaname shrimp samples from 3 locations, namely Bengkalis district, Bukit Batu district and Rupat district. So the prevalence of the research results obtained is 0%.